Carrying capacity of pelagic ecosystems of the Ross Sea (Antarctica) during summer: primary production processes and limiting factors. - MANGONI, OLGA; Conversano F.; Saggiomo V. (2013)
The Ross Sea is one of the most productive areas of the Southern Ocean; seasonal variations in biomass accumulation and production are very pronounced. Highest values of primary production are recorded in austral spring till early summer. During summer primary production sharply decreases and micro-nutrients limitation as well as deepening of the upper mixed layer have been invoked as major factors limiting phytoplankton growth. During austral summer 1996 and 2001 two oceanographic cruises were carried out in the Ross Sea within the framework of the PNRA. Primary production processes are presented for different environmental conditions during austral summer characterized by ice free waters and extensive ice coverage in offshore waters. In extensive pack ice coverage, the average Chlorophyll a (Chla) concentration was about three times the values recorded under ice-free conditions but the primary production was relatively lower. In situ primary production and photosynthetic parameters over few days show that in most of the area high primary production values occurs only in the first five meter of the water column and within the melting pack-ice. Notwithstanding the some values of phytoplankton biomass, water column stability, similar irradiance levels, photosynthetic capacity was suppressed in deeper layer indicating a low carrying capacity of pelagic ecosystem. In contrast to a very high variability in phytoplankton biomass and primary production, photosynthetic parameters vary within narrow ranges. Spatial and temporal distribution of biomass (Chla), in situ simulated primary production, photosynthetic parameters (PvsE) are presented in order to assess the carrying capacity and limiting factors of primary production of the Ross Sea, during austral summer, in different environmental conditions.